KEBIJAKAN PRESIDEN PRABOWO MEMBENTUK TIM SATGAS PERCEPATAN PERTUMBUHAN EKONOMI TINJAUAN YURIDIS ATAS KEWENANGAN EKSEKUTIF DAN KONSEKUENSI HUKUM ADMINISTRASI NEGARA - Wisnu Cahyo Apriliyadi; Mustofa Kamil; Muhammad Fajar Alfahimi; Aditya Putra Setyawan; Ahiruddin (CV. Lafadz Jaya, 2026)
President Prabowo Subianto’s policy to establish a Task Force (Satgas) for the Acceleration of Government Programmes to Support Economic Growth through Presidential Decree No. 4 of 2026 constitutes a strategic step within the architecture of national economic governance. This study analyses the legal basis for the formation of the task force from the perspective of administrative law, examines the President’s authority in forming task forces as policy instruments, and identifies the legal implications for the system of inter-governmental coordination. The research method employed is a normative legal approach utilising legislation, conceptual analysis, and case studies. The research findings indicate that the formation of the Task Force has a constitutional basis under Article 4(1) of the 1945 Constitution, which designates the President as the holder of executive power. However, the existence of a Task Force comprising 27 ministers and heads of agencies raises legal questions regarding the hierarchical relationship with ministries/agencies that are structurally under the coordination of coordinating ministers, as well as the potential for overlapping authority with other task forces that have been established previously. This study recommends the need for clear technical and operational regulations to minimise conflicts of authority and ensure accountability in the implementation of the Task Force’s duties within the framework of good governance.